Case of a Newborn with Prenatal Diagnosis of a Meningocele Reclassified as Benign Cystic Teratoma - Maheshwari, Abhinav; Malwade, Sudhir; Mane, Shailaja; Kokkirala, Harika; Suresh, Saurabh (Journal of Neonatal Surgery, 2025)
Background: Spinal masses in neonates, such as meningoceles and teratomas, can present diagnostic dilemmas due to similar imaging characteristics. Benign cystic teratomas, while rare, can mimic meningocele on imaging, necessitating histopathological confirmation for accurate diagnosis. We report a case of a male newborn initially diagnosed with meningocele that was later reclassified as a benign cystic teratoma after surgical intervention. Further insights from literature highlight the complexities of differential diagnosis and management of these masses. Case summary: The case of a male newborn delivered at 38 weeks of gestation, initially diagnosed with a meningocele on prenatal imaging. Mother was an operated case of Meningocele at 6 month of age with VP Shunt insitu. Post-delivery, a large, globular, midline sacrococcygeal mass covered by smooth, thin skin was noted .Postoperative histopathology reclassified the lesion as a benign cystic teratoma. Conclusion: This case emphasizes the diagnostic challenges posed by overlapping radiological features of spinal masses and highlights the importance of histopathology in confirming the diagnosis. Surgical excision led to an uneventful recovery, underscoring the value of multidisciplinary care in achieving favorable outcomes.